A phased mission approach to fault propagation - Lloyd, Michael D. (2014)
On complex systems with built-in health management systems, the faults diagnosed during a mission can number in the tens of thousands. When these faults are evaluated, many are found to be false. This work has, therefore, developed a technique by which diagnosed faults can be evaluated using known system data and a system modelling technique to automatically verify their legitimacy.